The Emergence of the Socialist Movement in the Maritimes, 1899-1916 - Frank, David; Reilly, Nolan (Labour / Le Travail, 1979)
In the years after 1899 a small but vigorous socialist movement emerged in Canada's Maritime Provinces. This article describes the origins, activities, ideas and personalities of the early socialist movement in the region. The socialists gained support in the region's industrial centres and coal-mining districts and contributed a proportionate share of the national support enjoyed by the Socialist Party of Canada and the newspaper Cotton's Weekly. The article concludes that early Canadian socialism found an important following outside western Canada and that "conservatism" is not an adequate explanation of the history of the Maritimes.